Racist States of Mind. - Keval, Narendra (Karnac Books, 2016)
Racism is a treacherous phenomenon with many faces that allow it a remarkable capacity to co-exist with support for ethnic and cultural diversity. In both its subtle and virulent forms, racist states of mind reveal a bewildering mix of anxieties, feelings and fantasies about the real complexities of life and living that a recognition of difference and diversity can potentially bring forth. These are often expressed in a nostalgic gaze that is infused with a toxic interplay of grievance, murderous rage, and vengeful feelings and fantasies that have resulted from a real or imagined narcissistic injury to the self, group, or nation. In a racist state of mind grief and mourning for such losses are replaced by manic omnipotent states which aim to triumph over feelings of powerlessness through an inflated sense of self that claims superiority over others who are made to become the bearers of inadequacy or inferiority. The compensatory excitements of hatred, cruelty, and violence can lead to a collapse of a triangular mental space that damages the capacity for curiosity and concern for others. The tragic consequences of this psychic assault is a rupture at the very core of identity and the self which aims to thwart the desires and emotional freedom of others. In this book the author explores the quality of thinking in racist states of mind and suggests that the fantasy dramas of the primal scene provide an essential framework in which racial and racist fantasies exist as deep structures of thought and feeling. These are intrinsic to psychic life and functioning, universally present in contemporary culture as well as the consulting room where they constitute the passions of the transference. The author explores the predicaments and challenges of engaging with these states of mind in the consulting room, group, organisational, and societal life.